Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am having difficulty understanding how this follows.

$$(\log n)^{ (\log n) } = 2^{(\log n)(\log (\log n))} = n^{\log \log n}$$

Which logarithmic identities are used to go through each equality?

e.g. how do you first go from

$$(\log n)^{ (\log n) } = 2^{(\log n)(\log (\log n))}$$

and then to

$$2^{(\log n)(\log (\log n))} = n^{\log \log n}$$

(The log base must be 2 or else this equality won't hold)

share|improve this question
What base is the logarithm? –  Argon Jul 28 '12 at 18:10
The log base must be 2 or else it won't hold. –  Not a NaN notha Jul 28 '12 at 18:11
Are you sure it is not base 2? –  Argon Jul 28 '12 at 18:15
As T. Webster said, it must be base 2 in spite of the OP having stated that it is base 10...or else the equality doesn't hold. –  DonAntonio Jul 28 '12 at 18:30
@DonAntonio For clarification, the edits occurred after I asked if the base is 2. –  Argon Jul 28 '12 at 20:48

3 Answers 3

up vote 4 down vote accepted

I'm assuming the base is $2.$ Otherwise the equality doesn't hold.

$$2^{(\log n)(\log (\log n))} = 2^{(\log (\log n)) (\log n)} = (2^{(\log (\log n))})^{(\log n)}$$ and $$ 2^{(\log (\log n))} = \log n $$ because $$ 2^{\log x} = x.$$

Edit: to reflect the update in the question:

$$ 2^{(\log n)(\log (\log n))} = (\color{blue}{2^{(\log n)}})^{(\log (\log n))} = \color{blue}{n}^{{(\log (\log n))}} = n^{\log \log n} $$ because again $$ 2^{\log n} = n.$$

share|improve this answer
@T.Webster we have: $2^{ab} = 2^{ba} = (2^{a})^{b}.$ –  user2468 Jul 28 '12 at 18:06
Thanks I can accept answer after waiting several minutes. –  Not a NaN notha Jul 28 '12 at 18:07
@T.Webster it's equality. So you can either start from the right hand side or the left hand side. I started from the right hand side. $$2^{\log n \log \log n} = 2^{(\log \log n)\log n} = (2^{\log \log n})^{\log n} = (\log n)^{\log n}.$$ –  user2468 Jul 28 '12 at 18:10
@T.Webster wait few minutes, read other possible answers and then try to write down (with pencil & paper) the whole proof step by step. –  user2468 Jul 28 '12 at 18:12
@J.D. , isn't your answer taking $\,\log =\log_2\,$ ? –  DonAntonio Jul 28 '12 at 18:19

For any $$1\neq a\in\Bbb R^+\,\,,\,\,x^y=a^{y\log_ax}\,\,,\,\text{whenever LHS is defined. }$$

Thus, $$(\log n)^{\log n}=2^{\log n\,\log_2(\log n)}$$

So your equality follows if the logarithm here is taken in base $\,2\,$ and not $\,10\,$ , as you wrote...

share|improve this answer
+1. My answer assumes base 2. –  user2468 Jul 28 '12 at 18:21


$$y=\log_2^{\log_2 n} n$$

Taking the logarithm (in base 2) of both sides

$$\log_2 y=\log_2 n \log_2 \log_2 n$$

Now, remember that $2^{\log_2 n}=n$. Thus

$$y=2^{\log_2 y}=2^{\log_2 n \log_2 \log_2}$$

Also recall that $a^{bc}=(a^b)^c$. Thus

$$y=2^{\log_2 n \log_2 \log_2 n}=(2^{\log_2 n})^{\log_2 \log_2 n}=n^{\log_2 \log_2 n}$$

share|improve this answer
+1 This answer was also really clarifying. –  Not a NaN notha Jul 28 '12 at 18:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.